6
$\begingroup$

The only way I can show $$\cos(20^\circ)\cos(30^\circ)\cos(40^\circ)=\cos^2(10^\circ)\cos(50^\circ)$$ stinks of sweat and brute force:

If $\cos(10^\circ)=x$ then using $\cos(a+b) = \cos a \cos b - \sin a \sin b$ and $\cos^2 + \sin^2 = 1$ you get $$ \cos(20^\circ) = 2x^2-1\\ \cos(30^\circ) = 4x^3-3x \\ \cos(40^\circ) = 8x^4-8x^2+1\\ \cos(80^\circ) = 128x^8-256x^6+160x^4-32x^2+1 $$ Then $$ \sin(10^\circ) = 128x^8-256x^6+160x^4-32x^2+1 $$ and using $\sin (a+b) = \sin(a) \cos(b) + \cos a \sin b$ and $\sin(30^\circ)=\frac12$ you get $$ \sin(20^\circ)= 256x^9 -512x^7+320x^5-64x^3+2x \\ \cos(50^\circ)=(2x^2-1)(4x^x-3x) - \frac12(256x^9 -512x^7+320x^5-64x^3+2x)\\ \cos(50^\circ) = -128x^9+256x^7-152x^5+22x^3+2x $$ Now that we have all the needed values of cosines, we have to prove that $$ (2x^2-1)(4x^x-3x)(8x^4-8x^2+1)=x^2(-128x^9+256x^7-152x^5+22x^3+2x)\\ 64x^9-144x^7+112x^5-34x^3+3x=-128x^{11}+256x^9-152x^7+22x^5+2x^3 $$ The tool we have is that $\cos(30^\circ) = \frac{\sqrt{3}}{2}$ so $$x^3=\frac{\sqrt{3}/2+3x}{4} $$ We now have to use that replace the highest power of $x$ by 2 powers lower; for example, using $$x^{11} = \frac{3x^9}{4} + \frac{\sqrt{3}}{8}x^8$$ I had to do this replacement trick thirteen times (seven on the right side and six on the left) before I came to $$ -x^3 + \frac{\sqrt{3}x^2}{2} + \frac{3x}{4} = -x^3 + \frac{\sqrt{3}x^2}{2} + \frac{3x}{4} $$ And we come to the original question -- there has got to be an easier way to show this!

$\endgroup$
  • 1
    $\begingroup$ My first instinct was to use $\cos(x)=\frac{e^{x i}+e^{-x i}}{2}$. It will also involve some brute force, but perhaps it will clean up more rapidly than the work you already did. $\endgroup$ – JMoravitz Jun 7 '16 at 21:51
  • $\begingroup$ That does not seem to help -- I end up with equally messy expressions for both sides of the equality, and now the trick of knowing and using the value of $\cos\frac{\pi}{6}$ becomes a lot less clean. $\endgroup$ – Mark Fischler Jun 7 '16 at 21:58
4
$\begingroup$

Using degrees as a unit, $$ \cos20^{\circ}\cos30^{\circ} = \frac{1}{2}\left(\cos50^{\circ}+\cos10^{\circ}\right)$$ and by multiplying both sides by $\cos40^{\circ}$: $$ \cos20^{\circ}\cos30^{\circ}\cos40^{\circ} = \frac{1}{4}\left(\cos90^{\circ}+\cos10^{\circ}+\cos50^{\circ}+\cos30^{\circ}\right). $$ while the same approach leads to: $$ \cos10^{\circ}\cos10^{\circ}\cos50^{\circ} = \frac{1}{4}\left(\cos70^{\circ}+2\cos50^{\circ}+\cos30^{\circ}\right)$$ so it is enough to prove that: $$ \cos70^{\circ}+\cos50^{\circ}=\cos10^{\circ} $$ that follows from $\cos60^{\circ}=\frac{1}{2}$.

$\endgroup$
  • $\begingroup$ NIce. This is the sort of answer I was looking for. $\endgroup$ – Mark Fischler Jun 8 '16 at 5:52
  • $\begingroup$ @Micheal Rozenberg: thank you Micheal, I was too lazy to put a $\circ$ everywhere, but now we may remove the very first line, too. $\endgroup$ – Jack D'Aurizio Mar 21 '17 at 20:26
2
$\begingroup$

Perhaps multiply both sides by $\sin\left(20^{\circ}\right)$, so that \begin{align*} \text{LHS}= & \sin\left(20^{\circ}\right)\cos(20^{\circ})\cos(30^{\circ})\cos(40^{\circ})\\ = & \frac{1}{2}\sin\left(40^{\circ}\right)\cos(30^{\circ})\cos(40^{\circ})\\ = & \frac{1}{4}\sin\left(80^{\circ}\right)\cos(30^{\circ})\\ = & \frac{\sqrt{3}}{8}\cos\left(10^{\circ}\right), \end{align*} and \begin{align*} \text{RHS} & =\left(\sin\left(20^{\circ}\right)\cos(10^{\circ})\cos(50^{\circ})\right)\cos(10^{\circ})\\ & =\frac{1}{2}\sin\left(20^{\circ}\right)\left(\cos(40^{\circ})+\frac{1}{2}\right)\cos(10^{\circ})\\ & =\left(\frac{1}{4}\left(\sin\left(60^{\circ}\right)-\sin(20^{\circ})\right)+\frac{1}{4}\sin\left(20^{\circ}\right)\right)\cos(10^{\circ})\\ & =\frac{\sqrt{3}}{8}\cos\left(10^{\circ}\right). \end{align*}

$\endgroup$
0
$\begingroup$

I may have cheated, but whatever... gonna borrow an identity for a second...

$$\text{if } \alpha+\beta+\gamma = 180 \text{ then } \frac{\sin(2\alpha) + \sin(2\beta) + \sin(2\gamma)} 2 = 2\sin\alpha\sin\beta\sin\gamma$$

$$\cos(20)\cos(30)\cos(40)=\sin(70)\sin(60)\sin(50)$$

Interestingly, this means

$$\cos(20)\cos(30)\cos(40)=\frac{\sin(140)+\sin(120)+\sin(100)}4$$

$$\implies\sin(140)+\sin(120)+\sin(100)=4\cos^2(10)\cos(50)$$

I'm not sure where you'd go from there, possibly try to put the RHS into a form where we can apply the identity?

$\endgroup$
0
$\begingroup$

$$\cos10^\circ=\sin80^\circ=2\sin40^\circ\cos40^\circ=2(2\sin20^\circ\cos20^\circ)\cos40^\circ$$

So, the problem reduces to $$\cos30^\circ=4\cos10^\circ\sin20^\circ\cos50^\circ$$

Now use prove that : cosx.cos(x-60).cos(x+60)= (1/4)cos3x

$\endgroup$
0
$\begingroup$

There is a formal, purely multiplicative proof.

All the information needed is:

  • $\cos(20) \cos(40) \cos(80)$ and $\sin(20) \sin(40) \sin(80)$ have known values (in fact we only need the product of $\tan(20) \tan(40)\tan(80)$)
  • $\cos (30)$ is known
  • basic identities $\sin(x) = \cos(90 - x)$ and $\sin(2x) = 2 \sin x \cos x$

Multiply the alleged formula by $\cos 80 = \sin 10$ , using ( ) to denote known quantities.

c20 c30 c40 c80 ?= s10 c10 c10 c50

(c20 c40 c80) (c30) ?= s10 c10 c10 c50

(c20 c40 c80) (c30) ?= s10 c10 s80 s40

(c20 c40 c80) (c30) ?= (s20 s40 s80) / 2

which is true knowing the values of the (20 40 80) products. The identity is equivalent to the product $\tan(20) \tan(40) \tan(80) = \sqrt{3}$ and does not need separate knowledge of the sine and cosine products.

Until a better reference comes along for the 20-40-80 products, here is a misnamed one, http://en.wikipedia.org/wiki/Morrie%27s_law

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.